Negative electrode sheet, secondary battery, and electric device
Patent Information
- Application Number
- CN202611223762.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-27
AI Technical Summary
本申请通过在负极的集流体上设置含有金属有机框架材料的负极涂层,可以诱导锂离子的均匀沉积,抑制锂枝晶的生成,从而提高电池的能量密度;
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the field of secondary battery technology, specifically to a negative electrode sheet, a secondary battery, and an electrical device. Background Technology
[0002] Currently, with the increasing demand from new energy vehicle users for longer driving range, the energy density of secondary batteries needs to be further improved.
[0003] Existing electrodeless batteries only have a copper current collector on the negative electrode side, without pre-filling negative electrode active materials such as graphite or lithium metal. During charging, lithium ions are completely extracted from the positive electrode and directly deposited on the copper foil surface. Copper foil has lithium-repellent properties, and the overpotential for lithium nucleation on the copper surface is relatively high. Lithium easily nucleates unevenly at defect sites on the copper foil surface, and the protrusions generate a sharp electric field effect, inducing lithium to grow longitudinally in a directional manner to form dendrites. This makes electrodeless batteries more prone to lithium dendrite formation than traditional lithium-ion batteries. As the cycle progresses, the total amount of active lithium available for charge transfer in the battery decreases, resulting in a reduction in the energy stored per unit mass. Summary of the Invention
[0004] Based on the deficiencies of the existing technology, the purpose of this application is to provide a negative electrode sheet, a secondary battery, and an electrical device.
[0005] To achieve the above objectives, the technical solution adopted in this application is as follows: The first aspect of this application provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode coating disposed on at least one side surface of the negative electrode current collector, the negative electrode coating comprising a metal-organic framework material, the Young's modulus of the negative electrode coating being EGPa, the average pore size of the metal-organic framework material being rnm, and the negative electrode sheet satisfying: E / r being 0.7~33.
[0006] A second aspect of this application provides a secondary battery, including the aforementioned negative electrode, as well as a positive electrode, an electrolyte, and a separator.
[0007] A third aspect of this application provides an electrical device including the aforementioned secondary battery.
[0008] Compared with the prior art, the beneficial effects of this application are as follows: This application improves the energy density of the battery by setting a negative electrode coating containing a metal-organic framework material on the current collector of the negative electrode, which can induce uniform deposition of lithium ions and suppress the formation of lithium dendrites. This application achieves a better balance between the lithium storage space and structural strength of the negative electrode coating by comprehensively controlling the average pore size (rnm) of the metal-organic framework material and the Young's modulus (EGPa) of the negative electrode coating within a suitable range. This allows the negative electrode sheet to be used in secondary batteries while maintaining both the energy density and kinetic performance of the secondary battery. Detailed Implementation
[0009] To better illustrate the purpose, technical solution, and advantages of this application, the following description, in conjunction with specific embodiments and comparative examples, aims to provide a detailed understanding of the content of this application, rather than to limit it. All other embodiments obtained by those skilled in the art without inventive effort are within the protection scope of this application.
[0010] The technical features described in this application in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions.
[0011] It should be understood that, unless otherwise specified, the numerical ranges involved in this application are considered continuous, including the minimum and maximum values of the range, and every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the maximum and minimum values of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed in this application should be understood to include any or all of the subranges to which they are included.
[0012] It should be understood that this application does not impose any particular restrictions on the specific dispersion or mixing methods.
[0013] The first aspect of this application provides a negative electrode sheet, which includes a negative electrode current collector and a negative electrode coating disposed on at least one side surface of the negative electrode current collector. The negative electrode coating includes a metal-organic framework material, the Young's modulus of the negative electrode coating is EGPa, the average pore size of the metal-organic framework material is rnm, and the negative electrode sheet satisfies: E / r is 0.7~33.
[0014] In a negative electrode-less secondary battery, negative electrode active material is usually not pre-placed on the negative electrode side. During the first charge, lithium ions released from the positive electrode are transported by the electrolyte and directly reduced and deposited on the surface of the negative electrode current collector to form a metallic lithium layer. During subsequent cycles, metallic lithium continues to undergo deposition and stripping behavior.
[0015] The inventors discovered that by setting a negative electrode coating containing a metal-organic framework material on the current collector of the negative electrode, they can induce uniform deposition of lithium ions and suppress the formation of lithium dendrites, thereby improving the energy density of the battery.
[0016] The inventors discovered that a larger average pore size (rnm) of the metal-organic framework (MOF) provides more lithium storage space. However, excessively large average pore size (rnm) weakens the structural strength of the MOF. When used as an anode in a secondary battery, the MOF is prone to collapse during repeated charge-discharge cycles, causing cracking of the anode coating, disrupting the integrity of the anode structure, affecting the efficient transport of electrons and ions, and reducing the kinetics of the secondary battery. Increasing the Young's modulus of the coating improves the overall structural strength of the coating, preventing structural collapse of the MOF during charge-discharge cycles, thereby reducing interfacial impedance and improving the kinetic performance of the secondary battery. This application, by comprehensively controlling the average pore size (rnm) of the MOF and the Young's modulus (EGPa) of the anode coating, keeps the E / r ratio within a suitable range, better balancing the lithium storage space and structural strength of the anode coating. This allows the anode to be used in secondary batteries while maintaining both energy density and kinetic performance.
[0017] For example, E / r can be a range of any one or any two of the following: 0.7, 1, 1.5, 1.9, 2, 3, 4, 4.2, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33.
[0018] In some embodiments, E / r is preferably 1.9 to 12.8. When E / r is within this preferred range, the negative electrode sheet used in a secondary battery can improve the overall performance of the secondary battery.
[0019] In some implementations, EGPa is 3GPa to 20GPa.
[0020] For example, EGPa can be any one or any combination of two of the following: 3GPa, 4GPa, 4.2GPa, 5GPa, 6GPa, 7GPa, 8GPa, 9GPa, 10GPa, 11GPa, 12GPa, 13GPa, 14GPa, 15GPa, 16GPa, 17GPa, 18GPa, 19GPa, and 20GPa.
[0021] The inventors of this application have discovered that a higher Young's modulus in the negative electrode coating makes it more prone to pulverization and / or interlayer delamination due to stress concentration caused by volume changes during charging and discharging. This leads to potential contact failure between the negative electrode coating and the negative electrode current collector, reducing the number of lithium sites available for reaction and thus decreasing the battery's energy density. Conversely, a lower Young's modulus weakens the overall structural strength of the negative electrode coating, making it more susceptible to cracking during charging and discharging, increasing interfacial impedance, and thus deteriorating the battery's kinetic performance. This application regulates the Young's modulus of the negative electrode coating to the aforementioned range. This not only buffers the volume changes of the negative electrode during charging and discharging, preventing interlayer delamination between the negative electrode coating and the negative electrode current collector, thus ensuring the availability of lithium sites for reaction and maintaining the battery's energy density, but also improves the overall structural strength of the negative electrode coating, preventing increased interfacial impedance due to cracking during charging and discharging, thereby improving the battery's kinetic performance.
[0022] This application does not impose any particular limitation on the means of controlling the Young's modulus EGPa of the negative electrode coating.
[0023] Specifically, the negative electrode coating may include a negative electrode binder. This application can control the Young's modulus of the negative electrode coating by adjusting the mass ratio of the metal-organic framework material to the negative electrode binder. The mass ratio of the metal-organic framework material to the negative electrode binder in the negative electrode coating can be (6.1~16):1. Introducing a negative electrode binder into the negative electrode coating allows it to form a continuous phase, encapsulating the metal-organic framework material and transferring stress, thereby increasing the crosslinking network density of the negative electrode coating. The smaller the mass ratio of the metal-organic framework material to the negative electrode binder in the negative electrode coating, the larger the Young's modulus of the negative electrode coating.
[0024] The negative electrode binder may include binders conventional in the battery industry. For example, the negative electrode binder includes at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polyimide (PI), polyacrylic acid (PAA), polyacrylate, polyolefin, sodium carboxymethyl cellulose (CMC), and sodium alginate.
[0025] Specifically, the negative electrode coating may further include reinforcing agents, including at least one selected from graphene, carbon nanotubes, conductive carbon black, conductive graphite, and carbon fiber. The mass percentage of the reinforcing agent in the negative electrode coating is 0-10%, preferably 0.5-4.9%. This application can control the Young's modulus of the negative electrode coating by adjusting the mass percentage of the reinforcing agent in the negative electrode coating. The reinforcing agent itself has a high modulus and can form rigid support points in the negative electrode coating. The higher the mass percentage of the reinforcing agent in the negative electrode coating, the higher the Young's modulus of the negative electrode coating.
[0026] In some of these implementations, EGPa is preferably 5GPa to 15GPa.
[0027] In some implementations, rnm is 0.5nm to 5nm.
[0028] For example, rnm can be any one or any combination of 0.5nm, 1nm, 1.5nm, 2nm, 2.5nm, 3nm, 3.5nm, 4nm, 4.5nm, 5nm.
[0029] The inventors of this application have discovered that the smaller the average pore size of a metal-organic framework (MOF) material, the less lithium storage space it provides, leading to a decrease in battery energy density. Conversely, the larger the average pore size of an MOF material, the weaker its structural strength, making it prone to structural collapse during battery charging and discharging. This, in turn, makes the negative electrode more susceptible to cracking, affecting the transport rate of ions and electrons at the negative electrode and thus deteriorating the battery's kinetic performance. This application controls the average particle size of the MOF material to the aforementioned range, ensuring sufficient lithium storage space and thus maintaining battery energy density, while also preserving the structural strength of the MOF material. This prevents the negative electrode from cracking during battery charging and discharging, ensuring the transport rate of ions and electrons at the negative electrode and improving the battery's kinetic performance.
[0030] This application does not impose any particular limitation on the means of controlling the average pore size (rnm) of the metal-organic framework material.
[0031] In some embodiments, the metal-organic framework material is formed by a thermal reaction of a soluble metal salt and an organic ligand in a solvent, wherein the solvent includes at least one of water and an organic solvent. The average pore size (nm) of the metal-organic framework material can be controlled by adjusting the type of organic ligand and / or the temperature of the thermal reaction. The more carbon elements in the structure of the organic ligand, the larger the average pore size of the metal-organic framework material; the higher the temperature of the thermal reaction, the larger the average pore size of the metal-organic framework material. The temperature of the thermal reaction can be 60°C to 200°C.
[0032] The molar ratio of the soluble metal salt to the organic ligand is (1~5):1, for example, it can be any one or any combination of two of the following: 1:1, 2:1, 3:1, 4:1, 5:1; the solvent includes at least one of N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, methanol, ethanol, acetonitrile, deionized water, and dimethyl sulfoxide; the ratio between the mass of the organic ligand and the volume of the solvent is (1~10) g:100 mL, for example, it can be 1 g:100 mL, 2:100 mL, 3:100 mL, etc. The ratio range is any one or any two of the following: 4:100mL, 5:100mL, 6:100mL, 7:100mL, 8:100mL, 9:100mL, 10:100mL; the thermal reaction time is 6h to 48h, for example, it can be any one or any two of the following: 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h, 26h, 28h, 30h, 32h, 34h, 36h, 38h, 40h, 42h, 44h, 46h, 48h.
[0033] Specifically, the preparation methods of the metal-organic framework materials include, but are not limited to, the following methods: A soluble metal salt and an organic ligand are added to a solvent at a molar ratio of (1~5):1, wherein the mass ratio of the organic ligand to the volume of the solvent is (1~10) g : 100 mL. After mixing thoroughly, the mixture is transferred to a reaction vessel for a solvothermal reaction. The reaction temperature of the solvothermal reaction is 60~200℃, and the reaction time is 6h~48h. After the reaction is completed, the reaction product is cooled to room temperature and washed 3~5 times alternately with a mixed alcohol solution and DMF, wherein the mixed alcohol solution is a mixture of methanol and ethanol. Then, it is vacuum dried at 80~150℃ for 6h~12h to obtain the metal-organic framework material.
[0034] In some of these implementations, rnm is preferably 1nm to 3nm.
[0035] In some embodiments, the compaction density of the negative electrode sheet is 0.8 g / cm³. 3 ~1.5g / cm 3 .
[0036] For example, the compaction density of the negative electrode sheet can be 0.8 g / cm³. 3 0.9g / cm 3 1g / cm 3 1.1g / cm 3 1.2g / cm 3 1.3g / cm 3 1.4g / cm 31.5g / cm 3 The range consisting of any one or any two of them.
[0037] In some embodiments, the metal-organic framework material comprises an organic ligand and a metal ion, wherein the organic ligand has a structural formula containing a conjugated group, and the conjugated group includes at least one of a benzene ring, a fused ring, and a carbon-carbon double bond group, and the organic ligand has a structural formula containing at least three conjugated groups.
[0038] The inventors of this application have discovered that the more conjugated groups in the structural formula of the organic ligand, the higher the conductivity of the negative electrode coating.
[0039] In some embodiments, the organic ligand includes a carboxylic acid-containing organic ligand and a nitrogen-containing heterocyclic organic ligand, wherein the carboxylic acid-containing organic ligand includes at least one of terephthalic acid and trimesic acid, and the nitrogen-containing heterocyclic organic ligand includes at least one of 2-methylimidazole and bipyridine.
[0040] In some embodiments, the metal ions include at least one selected from aluminum ions, zirconium ions, zinc ions, and copper ions.
[0041] The inventors of this application have discovered that when the metal ions in the metal-organic framework material are aluminum ions and / or zirconium ions, the structural stability of the metal-organic framework material is higher.
[0042] In some embodiments, the metal-organic framework material includes at least one of the Lavasil framework series materials and the zeolite-like imidazole framework series materials.
[0043] In some embodiments, the negative electrode coating further includes doping elements.
[0044] In some embodiments, the doping element includes at least one of nitrogen, boron, sulfur, and phosphorus.
[0045] In some embodiments, the dopant element has a mass percentage content of 0.5% to 5% in the negative electrode coating.
[0046] For example, the mass percentage of the dopant element in the negative electrode coating can be any one or a combination of any two of the following: 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, and 5%. The inventors of this application have discovered that introducing dopant elements into the negative electrode coating can effectively improve its conductivity.
[0047] In some embodiments, the thickness of the negative electrode coating is 1 μm to 10 μm.
[0048] For example, the thickness of the negative electrode coating can be any one or any combination of 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm.
[0049] The inventors of this application have discovered through research that adjusting the thickness of the negative electrode coating to the above-mentioned range can not only make the lithium ion transport path moderate and ensure the dynamic performance of the battery, but also provide sufficient space to induce uniform lithium ion deposition, reduce the amount of lithium plating on the negative electrode, and improve the energy density of the battery.
[0050] In some embodiments, the porosity of the negative electrode coating is 20% to 60%.
[0051] For example, the porosity of the negative electrode coating can be any one or any combination of 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60%.
[0052] The inventors of this application have discovered that the higher the porosity of the negative electrode coating, the lower its mechanical strength, making the negative electrode sheet prone to cracking during battery charging and discharging, thus deteriorating the battery's kinetic performance. Conversely, the lower the porosity of the negative electrode coating, the less lithium storage space it provides, resulting in lower battery energy density. This application controls the porosity of the negative electrode coating to the aforementioned range, which can both ensure the mechanical strength of the negative electrode coating, making the negative electrode sheet less prone to cracking during battery charging and discharging, thereby ensuring the battery's kinetic performance, and provide sufficient lithium storage space, thereby improving the battery's energy density.
[0053] In some embodiments, the negative current collector comprises a copper foil, which includes at least one of porous copper foil, etched copper foil, and copper foil with a lithiophilic coating on its surface, wherein the lithiophilic coating includes at least one of carbon and gold.
[0054] The inventors of this application have discovered through research that the porous structure or rough surface of the negative electrode current collector can increase its bonding force with the negative electrode coating; the lithiophilic coating of the negative electrode current collector can further reduce the nucleation overpotential of lithium and guide the uniform deposition of lithium ions.
[0055] In some embodiments, the negative electrode coating may further include a negative electrode dispersant, which includes at least one of hydroxymethyl cellulose, acrylics, acrylates, polyether esters, phosphate esters, small molecule alkanolamines, polyurethanes, modified styrene / maleic anhydride, nitrile rubber (HNBR), and polyvinylpyrrolidone (PVP). Based on the total mass of the negative electrode coating, the mass percentage of the negative electrode dispersant is 0.3% to 1.5%.
[0056] The method for preparing the negative electrode sheet includes, but is not limited to, the following methods: The components of the negative electrode coating are added to a solvent and mixed to obtain a negative electrode coating slurry. The prepared negative electrode coating slurry is uniformly coated on at least one side of the negative electrode current collector and dried to obtain the negative electrode sheet.
[0057] In the above-mentioned method for preparing the negative electrode sheet, the solvent includes the negative electrode coating slurry with a solid content of 30-60%, and the drying process includes the following steps: pre-drying stage: hot air drying at 60-80℃ for 10-30 min to remove most of the solvent; main drying stage: vacuum drying at 100-120℃ for 6-12 h to completely remove the residual solvent.
[0058] A second aspect of this application provides a secondary battery comprising the aforementioned negative electrode, a positive electrode, a separator, and an electrolyte.
[0059] In some embodiments, the compaction density of the positive electrode is 3 g / cm³. 3 ~4.2g / cm 3 .
[0060] For example, the compaction density of the positive electrode sheet can be 3 g / cm³. 3 3.1g / cm 3 3.2g / cm 3 3.3g / cm 3 3.4g / cm 3 3.5g / cm 3 3.6g / cm 3 3.7g / cm 3 3.8g / cm 3 3.9g / cm 3 4g / cm 3 4.1g / cm 3 4.2g / cm 3 The range consisting of any one or any two of them.
[0061] This application regulates the compaction density of the positive electrode sheet to the above-mentioned range, which can ensure the wetting effect of the electrolyte on the positive electrode sheet, improve the lithium ion transport efficiency, and thus improve the dynamic performance of the secondary battery; at the same time, it can ensure the content of positive electrode material in the positive electrode sheet and improve the energy density of the secondary battery.
[0062] In some embodiments, the positive electrode sheet includes a positive electrode material layer, the positive electrode material layer includes a positive electrode material, and the particle size Dv50 of the positive electrode material is 3μm~12μm.
[0063] For example, the particle size Dv50 of the positive electrode material can be any one or any combination of 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, and 12μm.
[0064] The inventors of this application have discovered through research that by adjusting the particle size Dv50 of the cathode material to the above-mentioned range, the transport path of lithium ions in the solid phase of the cathode material particles can be moderate, thereby ensuring the dynamic performance of the battery; at the same time, the specific surface area of the cathode material is moderate, reducing the side reactions between the cathode material and the electrolyte, reducing the consumption of active lithium, thereby ensuring the energy density of the battery.
[0065] In some embodiments, the cathode material includes at least one of lithium manganese iron phosphate, lithium iron phosphate, and nickel-cobalt ternary materials.
[0066] In some embodiments, the positive electrode material is at least one of lithium manganese iron phosphate and lithium iron phosphate, and the thickness of the negative electrode coating is 1 μm to 4 μm. The inventors of this application have discovered that when the positive electrode material is selected from lithium iron phosphate or lithium manganese iron phosphate, the battery's operating voltage platform is stable, volume expansion is small, the lithium intercalation process on the negative electrode side is relatively mild, and the battery's kinetic performance is good. The thickness of the negative electrode coating is preferably 1 μm to 4 μm, which can improve the battery's energy density while ensuring its kinetic performance.
[0067] In some embodiments, the positive electrode material is a nickel-cobalt ternary material, and the thickness of the negative electrode coating is 3μm~8μm.
[0068] The inventors of this application have discovered through research that when the positive electrode material is selected from nickel-cobalt ternary materials, the battery has a high working voltage and a large specific capacity, resulting in a high energy density. This leads to an increase in the lithium intercalation pressure on the negative electrode side, making it easier to induce lithium dendrite growth. In this case, the thickness of the negative electrode coating is preferably 3μm~8μm, which can improve the battery's dynamic performance while ensuring the battery's energy density.
[0069] In some embodiments, the surface of the positive electrode material is provided with a coating layer, the thickness of which is 1 nm to 10 nm.
[0070] For example, the thickness of the coating layer can be any one or any combination of 1nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, and 10nm.
[0071] The inventors of this application have discovered that by adjusting the thickness of the coating layer to the aforementioned range, it is possible to ensure the diffusion distance of lithium ions in the cathode material particles and the proportion of cathode material in the cathode material layer, thereby ensuring the energy density of the battery. Furthermore, the coating layer can form a continuous and uniform conductive network in the cathode material layer, thereby improving the conductivity of the cathode material and improving the battery's kinetic performance.
[0072] In some embodiments, the cathode material layer includes a dopant element, which includes at least one of Al, Mg, Ti, Zr, B, and Y; the mass percentage of the dopant element in the cathode material layer is 0.1% to 3%.
[0073] For example, the mass percentage of the dopant element in the cathode material layer can be any one or any combination of 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, and 3%.
[0074] The inventors of this application have discovered that by controlling the content of doped elements in the cathode material layer to the above-mentioned range, not only can the proportion of cathode material in the cathode material layer be guaranteed, thereby ensuring the energy density of the battery, but also the lithium-ion transport path can be optimized, thereby improving the dynamic performance of the battery.
[0075] In some embodiments, the cathode material includes lithium iron phosphate, which comprises ultra-large particles, large particles, and small particles. The ultra-large particles have a particle size of 3-15 μm, the large particles have a particle size of 1 μm-3 μm, and the small particles have a particle size of 60 nm-200 nm.
[0076] For example, the particle size of the ultra-large particles can be any one or a combination of any two of the following: 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm, 10.5μm, 11μm, 11.5μm, 12μm, 12.5μm, 13μm, 13.5μm, 14μm, 14.5μm, and 15μm. The particle size of the large particles can be any one or a combination of any two of the following: 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, and 2μm. The particle size can be any one or any combination of two of the following: 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, and 200nm.
[0077] The inventors of this application have discovered that using a combination of large-particle lithium iron phosphate and small-particle lithium iron phosphate can increase the compaction density of the cathode sheet, thereby improving the energy density of the battery. At the same time, it can shorten the transport path of lithium ions between cathode material particles and improve the dynamic performance of the battery.
[0078] In some embodiments, the positive electrode material layer further includes a positive electrode conductive agent and a positive electrode binder.
[0079] Specifically, the positive electrode conductive agent may include conductive agents conventional in the battery field, such as at least one of conductive carbon black, conductive graphite, graphene, carbon nanotubes, and carbon fibers.
[0080] Specifically, the positive electrode binder is used to improve the adhesion between positive electrode material particles and the adhesion between the positive electrode material and the positive electrode current collector. The positive electrode binder may include binders conventional in the battery industry. For example, the positive electrode binder includes at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polyimide (PI), polyacrylic acid (PAA), polyacrylate, polyolefin, sodium carboxymethyl cellulose (CMC), and sodium alginate.
[0081] In this application, based on the total mass of the positive electrode material layer, the mass percentage of the positive electrode material is 92% to 98%, the mass percentage of the positive electrode binder is 1% to 4%, and the mass percentage of the positive electrode conductive agent is 1% to 4%.
[0082] For example, based on the total mass of the positive electrode material layer, the mass percentage of the positive electrode material can be any one or any two of 92%, 93%, 94%, 95%, 96%, 97%, and 98%, the mass percentage of the positive electrode binder can be any one or any two of 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, and 4%, and the mass percentage of the positive electrode conductive agent can be any one or any two of 1%.
[0083] In some embodiments, the positive electrode includes a positive current collector, at least one surface of which is coated with the positive electrode material layer.
[0084] The positive current collector can be a metal foil or a composite current collector. For example, the metal foil may include aluminum foil. The composite current collector may include a substrate layer and a metal layer formed on at least one surface of the substrate layer. The composite current collector can be obtained by forming a metal material on a polymer substrate. The substrate layer is a polymer material, such as at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE). The metal layer may be made of at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy.
[0085] In this application, the positive electrode sheet can be prepared according to conventional methods in the art, for example, dispersing the components of the positive electrode material layer in a solvent to obtain a positive electrode slurry, coating the positive electrode slurry onto at least one surface of the positive electrode current collector, and then drying, rolling, and cutting to obtain the positive electrode sheet.
[0086] The preparation method of the positive electrode sheet includes, but is not limited to, the following methods: adding each component of the positive electrode material layer into a solvent and stirring evenly to obtain a positive electrode slurry with a solid content of 65-75%; uniformly coating the positive electrode slurry onto the positive electrode current collector, and obtaining the positive electrode sheet by drying, rolling, and cutting.
[0087] In some embodiments, the viscosity of the electrolyte at 25°C is 3 mPa·s to 15 mPa·s.
[0088] For example, the viscosity of the electrolyte at 25°C can be any one or a combination of any two of the following: 3 mPa·s, 4 mPa·s, 5 mPa·s, 6 mPa·s, 7 mPa·s, 8 mPa·s, 9 mPa·s, 10 mPa·s, 11 mPa·s, 12 mPa·s, 13 mPa·s, 14 mPa·s, and 15 mPa·s. This application controls the viscosity of the electrolyte at 25°C to the above range, which ensures the lithium-ion transport rate, thereby guaranteeing the battery's kinetic performance, and also makes the electrolyte less prone to decomposition, reducing the consumption of active lithium, thereby improving the battery's energy density.
[0089] In some embodiments, the electrolyte comprises a lithium salt; the lithium salt comprises at least one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium perchlorate, lithium tetrafluoroborate, lithium dioxalate borate, lithium difluorooxalate borate, lithium trifluoromethanesulfonate, lithium bis(fluoromethanesulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate, wherein the concentration of the lithium salt in the electrolyte is 0.8 mol / L to 1.5 mol / L.
[0090] For example, the concentration of lithium salt in the electrolyte can be any one or any combination of 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, and 1.5 mol / L.
[0091] This application regulates the concentration of lithium salt in the electrolyte to the above-mentioned range, which can promote lithium-ion transport, improve the dynamic performance of the battery, and provide sufficient active lithium to improve the energy density of the battery.
[0092] In some embodiments, the electrolyte includes a solvent.
[0093] In some embodiments, the solvent includes at least one selected from carbonate solvents, carboxylic acid ester solvents, ether solvents, sulfone solvents, nitrile solvents, and phosphate ester solvents. The carbonate solvents include dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate; the carboxylic acid ester solvents include at least one selected from methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), and 1,4-butyrolactone (GBL); the ether solvents include at least one selected from ethylene glycol dimethyl ether and tetrahydrofuran; and the sulfone solvents include at least one selected from sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).
[0094] In some embodiments, the electrolyte includes an additive, which includes at least one of vinylene carbonate, vinyl sulfate (DTD), 1,3-propanesulfonate lactone (PS), methanedisulfonate (MMDS), vinylene carbonate (VC), and fluorovinyl carbonate (FEC).
[0095] This application allows for the control of electrolyte viscosity by adjusting the composition of the solvent and the content of additives in the electrolyte. Specifically, the solvent is composed of ethylene carbonate (EC), methyl ethyl carbonate (EMC), and diethyl carbonate (DEC), and the additive is fluoroethylene carbonate (FEC). In the electrolyte, the volume ratio of ethylene carbonate (EC), methyl ethyl carbonate (EMC), diethyl carbonate (DEC), and fluoroethylene carbonate (FEC) is EC:EMC:DEC:FEC = (20~40):(30~50):(20~40):(2~10). By adjusting the ratio of each component of the solvent and the additive in the electrolyte to this range, the viscosity of the electrolyte at 25°C can be maintained in the range of 3 mPa·s to 15 mPa·s.
[0096] In this application, the preparation method of the electrolyte includes, but is not limited to, the following method: after mixing the solvent components evenly, adding additives, mixing evenly, then adding fully dried lithium salt, stirring and dissolving to prepare the electrolyte.
[0097] In some embodiments, the air permeability of the diaphragm is 200s / 100mL to 500s / 100mL.
[0098] For example, the permeability of the separator can be any one or a combination of any two of the following: 200s / 100mL, 250s / 100mL, 300s / 100mL, 350s / 100mL, 400s / 100mL, 450s / 100mL, and 500s / 100mL. By controlling the permeability of the separator within the above range, this application can ensure lithium-ion transport efficiency, reduce side reactions at the interface between the electrolyte and the positive and negative electrodes, and reduce the consumption of active lithium, thereby improving the battery's energy density while ensuring its kinetic performance.
[0099] This application does not impose any particular restrictions on the type of diaphragm; any well-known porous diaphragm with good chemical and mechanical stability can be selected.
[0100] In some embodiments, the diaphragm includes a base membrane, and at least one surface of the base membrane is provided with a coating. The base membrane may be made of at least one of polyethylene, polypropylene, and polyamide. The coating of the diaphragm may include at least one of aramid, polyimide, aluminum oxide, boehmite, titanium dioxide, silicon dioxide, zirconium dioxide, tin dioxide, magnesium oxide, zinc oxide, barium sulfate, boron nitride, aluminum nitride, and magnesium nitride.
[0101] In this application, the method for preparing the secondary battery includes, but is not limited to, the following methods: The positive electrode, separator, and negative electrode are stacked or wound in sequence so that the separator completely covers the positive and negative electrode to obtain a bare cell. The bare battery cell is installed into the casing, and electrolyte is injected into a glove box with a dew point ≤ -40℃ at a rate of 2.0~3.0 g / Ah. After the battery is left to stand at 20~25℃ for 12~36h, it is charged to 3.65V with a constant current of 0.05C, and then discharged to 2.5V with a current of 0.1C. This cycle is repeated twice to complete the formation. After vacuum sealing and secondary encapsulation, the battery is shaped to obtain the secondary battery.
[0102] A third aspect of this application provides an electrical device including the aforementioned secondary battery.
[0103] In this application, the Young's modulus EGPa of the negative electrode coating can be determined by the following method: Sample preparation: The secondary battery under test was discharged using a battery charging and discharging device. Discharge conditions: current 0.33C, cutoff lower limit voltage; The secondary battery was disassembled, the negative electrode was removed, and the negative electrode was cut into small pieces of 1cm×1cm to ensure that the coating surface was flat and free of contamination. Testing equipment: A nanoindenter (Agilent G200) equipped with a Berkovich diamond indenter was used.
[0104] Test parameters: Set the maximum indentation depth to 10%~20% of the coating thickness (to avoid substrate effect), keep the loading rate constant, hold time 10s, and unload rate the same as loading rate; During testing, a nanoindenter was used to perform indentation tests at at least five different locations on the coating surface; the load-unload curves were recorded, and the reduced modulus E of each indentation point was calculated according to the Oliver-Pharr method. r .
[0105] The Young's modulus E of the coating is obtained by formula 1 / E r =(1-ν 2 ) / E+(1−ν i 2 ) / E iCalculations are performed, where ν is the Poisson's ratio of the coating (taken as 0.3), and E... i and ν i These are Young's modulus (1141 GPa for diamond) and Poisson's ratio (0.07) of the indenter material, respectively.
[0106] Results processing: The average value of each test point is taken as the Young's modulus of the negative electrode coating, in GPa.
[0107] The average pore size (rnm) of the metal-organic framework material can be determined by the following method: The secondary battery under test was discharged using a battery charging and discharging device. The discharge conditions were: current 0.33C, cut-off lower limit voltage. The secondary battery was disassembled, the negative electrode was removed, and the negative electrode was immersed in DMC (dimethyl carbonate) at room temperature for 60 minutes. After that, it was removed and dried at room temperature with humidity ≤15%. The negative electrode coating on the surface of the current collector was scraped off and calcined at 400℃ for 3 hours. After washing and drying, a powder sample was obtained. A known amount of nitrogen gas was gradually introduced into the sample tube, and the pressure at which adsorption equilibrium was reached was recorded. By calculating the pressure change before and after each gas introduction, the amount of gas adsorbed by the sample at this pressure was obtained (relative pressure (P / P0) range: 1×10⁻⁶). -7 (Up to 0.995); gradually reduce the pressure (in 0.005 intervals), measure the desorption process to obtain a complete isothermal adsorption-desorption curve, and then calculate the average pore size of the sample in rnm.
[0108] The thickness of the negative electrode coating can be determined by the following method: 1) Use a battery charging and discharging device to discharge the secondary battery under test. Discharge conditions: current 0.33C, cut-off lower limit voltage; disassemble the secondary battery and remove the negative electrode. 2) Obtain cross-sectional SEM of the negative electrode sheet by cutting the CP, and measure the thickness of the negative electrode coating using scanning electron microscopy.
[0109] The porosity of the negative electrode coating can be determined by the following method: The electrode is cut into circular pieces with a radius r of 0.95 cm using an electrode punching machine. The total thickness of the electrode (denoted as L) and the thickness of the negative electrode current collector (denoted as L0) are measured using a thickness gauge. The volume of the negative electrode coating on the cut electrode is calculated as V = π × r. 2×(L-L0); Weigh the cut electrode using a balance with an accuracy of 0.00001 g and record the mass as m1. Immerse the electrode completely in hexadecane for 1 hour (completely submerged). Remove the electrode with tweezers and blot it dry with filter paper until a constant weight is achieved. Weigh the electrode again and record the mass as m2. Substitute the experimental data into the formula to calculate: ε=(m2-m1) / (V×ρ0)×100%, where ρ0 is the density of hexadecane, 0.7734 g / cm³. 3 The porosity of the negative electrode coating is obtained.
[0110] The mass percentage of doped elements in the negative electrode coating can be determined by the following method: (1) Sampling: Use a battery charging and discharging device to discharge the secondary battery under test at a constant current of 0.33C to the lower limit voltage (e.g., 2.5V) to bring the battery to a fully discharged state. Disassemble the battery in an inert atmosphere glove box (H2O<0.1ppm, O2<0.1ppm) and remove the negative electrode sheet. Washing and drying: Immerse the negative electrode sheet in dimethyl carbonate (DMC) for 60 minutes, replacing it with fresh DMC once during the process to thoroughly remove residual electrolyte. Remove the electrode sheet and place it in a vacuum oven to dry at 60°C for 2 hours, then transfer it to a glove box to cool naturally. Coating separation: In the glove box, use a non-metallic scraper (e.g., a PTFE scraper) to scrape the negative electrode coating off the negative electrode current collector and collect the powder sample, avoiding mixing with current collector debris; (2) Digestion (applicable to ICP-OES testing, such as determination of B, P, etc.): Accurately weigh 0.1 g (accurate to 0.0001 g) of the above powder sample into a polytetrafluoroethylene digestion vessel. Slowly add 5 mL of analytical grade nitric acid and 1 mL of analytical grade hydrogen peroxide, tighten the lid, and place it in a microwave digester for digestion; Example digestion program: heat to 180℃ and hold for 15 minutes, then heat to 210℃ and hold for 20 minutes; After digestion, cool to room temperature, transfer the digestion solution to a 100 mL volumetric flask, dilute to volume with ultrapure water, shake well and prepare for testing; At the same time, prepare a blank solution; (3) Direct injection (applicable to inert gas fusion method, such as determination of N and S): Use a balance of 1 / 1 million to weigh about 5 mg (accurate to 0.001 mg) of the scraped powder sample, wrap it in a tin bag, and put it into the autosampler; (4) Perform ICP testing on the digestion solution. Before testing, a standard solution must be prepared. The linear correlation coefficient of the standard concentration must be above 0.999 to be used as a normal standard. Dilute the 1000 mg / L standard solution with deionized water to different concentrations (generally 0, 1 mg / 100mL, 2 mg / 100mL, 3 mg / 100mL), select the element detection wavelength, and set the experimental conditions: According to the characteristics of the sample and the element to be detected, set the appropriate ICP instrument working conditions: gas flow rate 0.5L / min, power 1150W, select the element detection wavelength, and the content of the element in the sample can be read by the self-analysis function of the ICP testing software.
[0111] The compaction density of the negative electrode sheet can be determined by the following method: Discharge the battery to 2.5V at 0.33C, remove the empty battery, disassemble the negative electrode, soak the electrode in dimethyl carbonate (DMC) solution for 4 hours; then air dry. The pretreated negative electrode sheet is punched into circular pieces of a fixed area using a punching machine. The area is denoted as S0. Three circular pieces are taken as parallel samples, and their masses are weighed using an electronic balance. The average mass is recorded as m1. The total thickness of the negative electrode sheet and the thickness of the negative current collector in each of the three circular pieces are measured using a micrometer. The thickness of the negative electrode coating on the negative electrode sheet is obtained by subtracting the thickness of the negative current collector from the total thickness of the negative electrode sheet. The average mass is recorded as H. Finally, a suitable amount of deionized water is added to each of the three circular pieces, and the negative electrode coating is gently wiped off with lint-free paper to expose the negative current collector. The pieces are left to stand at room temperature (or dried) for 10 minutes. After the negative current collector is dry, the masses of the three negative current collectors are weighed, and the average mass is recorded as m0. The areal density of the electrode sheet is obtained by calculating (m1-m0) / S0 and converting the units, denoted as P. The unit of P is g / cm³. 2 Calculate the P / H ratio and convert the units to obtain the compaction density of the electrode, in g / cm³. 3 .
[0112] The compaction density of the positive electrode sheet can be determined by the following method: Discharge the battery to the lower limit voltage at 0.33C, remove the empty battery, disassemble the positive electrode, soak the electrode in dimethyl carbonate (DMC) solution for 4 hours; then air dry. The pretreated positive electrode sheet is punched into circular sheets of a fixed area using a punching machine. The area is denoted as S0. Three circular sheets are taken as parallel samples, and their masses are weighed using an electronic balance. The average mass is recorded as m1. The thickness of the positive electrode material layer (i.e., the total thickness minus the current collector) in each of the three circular sheets is measured using a micrometer. The average mass is recorded as H. Finally, a suitable amount of deionized water is added to each of the three circular sheets, and the positive electrode material layer is gently wiped away with lint-free paper to expose the positive electrode current collector. The sheets are then left to stand at room temperature (or dried) for 10 minutes. After the positive electrode current collector is dry, the masses of the three current collector sheets are weighed, and the average mass is recorded as m0. The areal density of the electrode sheet is calculated as (m1-m0) / S0 and the units are converted. This density is denoted as P, where P is in g / cm³. 2 Calculate the P / H ratio and convert the units to obtain the compaction density of the electrode, in g / cm³. 3 .
[0113] The mass content of dopant element M in the cathode material layer can be determined by the following method: Discharge the battery to the lower limit voltage at 0.33C, disassemble the secondary battery to obtain the positive electrode sheet, soak the positive electrode sheet in DMC (dimethyl carbonate) at room temperature for 60 minutes, take it out, dry it at room temperature with humidity ≤15%, and scrape off the positive electrode material powder on the surface of the current collector. Accurately weigh a certain amount of powder (e.g., 0.2g), disperse it in 20ml of water, add 10ml of nitric acid, mix thoroughly, and heat until the powder dissolves. Then, dilute the mixture to 100mL with water to obtain the test solution. Perform ICP testing on the test solution. Before testing, a standard solution must be prepared. The linear correlation coefficient of the standard concentration must be above 0.999 to be used as a normal standard. Dilute the 1000 mg / L standard solution with deionized water to different concentrations (generally 0, 1 mg / 100mL, 2 mg / 100mL, 3 mg / 100mL), and select the element detection wavelength. Set the experimental conditions: Based on the characteristics of the sample and the element to be detected, set appropriate ICP instrument operating conditions: gas flow rate 0.5L / min, power 1150W, and select the element detection wavelength, which depends on the element being tested (e.g., Fe wavelength 259.94nm, Mn wavelength 257.61nm, Ni wavelength 231.60nm, Mg wavelength 279.08nm). The wavelengths of Al (396.15 nm), Ti (323.452 nm), V (310.230 nm), Zr (336.12 nm), Nb (3094 nm), W (239.7 nm), and Y (371 nm) can be determined using the self-service analysis function of the ICP testing software. This allows us to read the content of elements in the sample, which is the mass content of doped element M in the cathode material layer.
[0114] The thickness of the coating layer can be determined by the following method: The lithium-ion battery was discharged to 2.5V at 0.33C, and then the positive electrode was removed. The positive electrode was dried at 40℃ for 4 hours, and then powder was scraped off. 1g of the powder was dispersed in 100ml of 98% alcohol and stirred for 30min. The dispersed powder was then dropped onto the copper foil on the TEM sample stage and sent into a TEM microscope for testing. Measurements were taken at appropriate magnification according to different thicknesses. Five different regions were measured and the average value was taken.
[0115] The thickness of the positive electrode material layer can be determined by the following method: 1) Use a battery charging and discharging device to discharge the secondary battery under test. Discharge conditions: current 0.33C, cut-off lower limit voltage; disassemble the secondary battery and remove the positive electrode. 2) Obtain cross-sectional SEM of the positive electrode sheet by cutting the CP, and measure the thickness of the positive electrode material layer in the positive electrode sheet using scanning electron microscopy.
[0116] The particle size Dv50 of the cathode material can be determined by the following method: (1) Use a battery charging and discharging device to discharge the secondary battery under test. Discharge conditions: current 0.33C, cutoff 2.5V. After recording the battery number / barcode, disassemble the discharged battery in a glove box (molar content of H2O ≤ 0.1ppm, molar content of O2 ≤ 0.1ppm), take out the positive electrode, soak the positive electrode in dimethyl carbonate (DMC) solution at room temperature for 4h, after soaking, take out the positive electrode and dry it in a vacuum environment, and scrape the positive electrode material powder on the surface of the electrode with a ceramic knife; (2) Take 1g of scraped positive electrode material powder as a sample, and use a laser particle size distribution measuring instrument (Mastersizer 3000) to measure the particle size distribution curve according to the particle size distribution laser diffraction method (refer to GB / T19077-2016 for specific steps). In the particle size distribution curve, the particle size value corresponding to the cumulative volume percentage reaching 50% is Dv50.
[0117] The viscosity c mPa·s of the electrolyte at 25°C can be determined by the following method: The secondary battery under test was discharged using a battery charging and discharging device under the following conditions: current 0.33C, cutoff voltage limit. Then, the battery was disassembled and the electrolyte collected in a glove box (H2O ≤ 0.1ppm, O2 ≤ 0.1ppm). There are three methods for collecting the electrolyte: After removing the battery cover, ① if there is free electrolyte, collect it into a 5mL sample tube using a pipette and seal it with adhesive tape to prevent leakage. ② if there is no free electrolyte, a hydraulic press (Beijing Heng'ao Technology Co., Ltd.'s FY-30 hydraulic press) can be used to continuously pressurize until free electrolyte appears. Collect the electrolyte into a sample tube and seal it. ③ Add an appropriate amount of dichloromethane extractant to the battery and record the dichloromethane content. After adding dichloromethane, put the battery into an aluminum-plastic bag and seal it with a heat sealer. Transfer it to an ultrasonic oscillator and oscillate for 12 hours to allow the electrolyte in the electrode to mix thoroughly with the dichloromethane. Then, use a pipette to draw the mixture of dichloromethane and electrolyte into a 5mL sample tube and seal the sample tube with sealing glue. The electrolyte was removed and tested using a Cambridge viscometer. The Cambridge viscometer is designed primarily based on electromagnetic oscillation viscosity detection technology, employing a magnetically levitated probe for viscosity measurement. Specifically, the electrolyte was placed in a beaker, and the sample temperature was controlled at 25°C for testing. The reading was taken after the displayed value stabilized.
[0118] The air permeability of the diaphragm can be determined by the following method: The secondary battery under test was discharged using a battery charge / discharge device under the following conditions: current 0.33C, cutoff voltage. The battery was then disassembled, and the separator was removed. The separator was soaked in DMC for 10 minutes and allowed to air dry. Subsequently, an air permeability tester was used at 25°C with a pressure of 1.21 kPa to measure the area through which 100 mL of air could pass, which was found to be 6.45 cm². 2 The time required for the sample diaphragm to be in place is expressed in seconds per 100 mL.
[0119] In this application, the fast-charging performance of the secondary battery can be determined by the following method: The secondary battery is charged at a constant current of 0.33C to the upper limit voltage, and then charged at a constant voltage until the current is less than or equal to 0.05C; then discharged at 0.33C to the lower limit voltage. The above steps are repeated 3 times, and the capacity discharged in the third cycle is taken as the battery discharge capacity. After resting for 10 minutes, discharge the secondary battery at 1C to the lower limit voltage. After resting for 10 minutes, charge the secondary battery at 0.33C to 10% SOC. Then charge the secondary battery at 4C to the upper limit voltage and record the time t0. Then charge in descending order at 0.4C: sequentially at 3.6C, 3.2C, 2.8C, 2.4C, 2.0C, 1.6C, 1.2C, 0.8C, and 0.4C. The cutoff condition for each charge is reaching the upper limit voltage. Record the time t1. t1-t0 is the fast charging time. The energy density of the battery can be determined by the following method: Using the aforementioned secondary battery as the test object, the mass of the secondary battery was weighed and recorded as m (in kg). The battery was placed in a fixture, and a force of 3000 N was applied. It was charged to the upper limit voltage with a constant current of 0.33 C, and then left to rest for 30 min. It was then discharged to the lower limit voltage with a constant current of 0.33 C, and left to rest for 30 min. This cycle was repeated 3 times. The discharge capacity (in Ah) and energy E (average value of three cycles, in Wh) were obtained and calculated according to the following formula: Energy density = E / m (in Wh / kg).
[0120] In this application, the lower limit voltage is 2.5V and the upper limit voltage is 3.65V.
[0121] To enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present application, and not all embodiments.
[0122] Unless otherwise specified, all experimental reagents and instruments used in this application are commonly used and ordinary reagents and instruments. Unless otherwise specified, all raw materials used in the embodiments and comparative examples of this application are commercially available, and the raw materials used in each parallel experiment are the same.
[0123] Example 1 The embodiment of the lithium-ion secondary battery described in this application includes a method for preparing the lithium-ion secondary battery comprising the following steps: S1, Preparation of the positive electrode Preparation of S11 and Lithium Iron Phosphate Using iron phosphate precursor, lithium carbonate, and glucose as raw materials, they were mixed in a molar ratio of 1:1.05:0.05, and an appropriate amount of anhydrous ethanol was added. The mixture was then milled at high speed, spray-dried, and sintered at 750℃ for 10h under a nitrogen atmosphere. After cooling, the mixture was crushed and sieved to obtain lithium iron phosphate with a particle size Dv50 of 4 μm. S12. Lithium iron phosphate (LiFePO4), acetylene black (acetylene black), and PVDF (PVDF) binder are mixed in a mass ratio of 95:3:2. NMP solvent is added, and the mixture is stirred under vacuum until the system is homogeneous to obtain a positive electrode slurry. The positive electrode slurry is then uniformly coated onto two opposing surfaces of a 12 μm thick aluminum foil current collector. After pre-drying at 80°C for 12 h, it is vacuum-dried at 120°C for 12 h. The resulting product is then rolled and slit to obtain a positive electrode sheet with a compaction density of 3.6 g / cm³. 3 ; S2, Preparation of the negative electrode S21. Using terephthalic acid and bipyridine as organic ligands, terephthalic acid, bipyridine, and copper nitrate were added to the solvent in a molar ratio of 1:1:2. The ratio of the total mass of the organic ligands to the volume of the solvent was 5 g : 100 mL. After mixing thoroughly, the mixture was transferred to a reaction vessel for a solvothermal reaction. The reaction temperature of the solvothermal reaction was 148℃, and the reaction time was 24 h. After the reaction was completed, the reaction product was cooled to room temperature and washed four times alternately with a mixed alcohol solution and DMF. The mixed alcohol solution was a mixture of methanol and ethanol. Then, it was vacuum dried at 120℃ for 10 h to obtain the metal-organic framework material.
[0124] S22. Copper foil was selected as the negative electrode current collector, and carbon nanotubes were selected as the reinforcing agent. The metal-organic framework material, reinforcing agent, binder PVDF, and dispersant PVP were dispersed in the solvent N,N-dimethylformamide to obtain a negative electrode coating slurry with a solid content of 45%. The mass ratio of the metal-organic framework material to the binder was 14.8:1. Based on the sum of the masses of the metal-organic framework material, reinforcing agent, binder PVDF, and dispersant PVP, the mass percentage of the reinforcing agent was 1%, and the mass percentage of the dispersant was 1%. The negative electrode coating slurry was coated on two opposite surfaces of the copper foil negative electrode current collector, pre-dried at 70℃ for 8 h, and then vacuum-dried at 110℃ for 8 h. After rolling and cutting, a compacted density of 1.2 g / cm³ was obtained. 3 The negative electrode.
[0125] S3. Preparation of electrolyte Ethylene carbonate (EC), dimethyl carbonate (DMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 30:50:20, and then fluoroethylene carbonate (FEC) was added. After mixing evenly, fully dried lithium salt LiPF6 was added, and the mixture was stirred and dissolved to prepare an electrolyte. The concentration of LiPF6 in the electrolyte was 1 mol / L, and the mass percentage of FEC in the electrolyte was 5%. S4. Preparation of the diaphragm Commercially available PE film was chosen as the separator; S5, Preparation of Lithium-ion Batteries The positive electrode, separator, and negative electrode are stacked or wound in sequence so that the separator completely covers the positive and negative electrode to obtain a bare cell. The bare battery cell is installed into the housing, and electrolyte is injected in a glove box with a dew point ≤ -40℃ at a rate of 2.5 g / Ah. After the battery is left to stand at 25°C for 24 hours, it is charged to 4.25V with a constant current of 0.05C, and then discharged to 2.5V with a current of 0.1C. This cycle is repeated twice to complete the formation. After vacuum sealing and secondary encapsulation, the battery is shaped to obtain the secondary battery.
[0126] Examples 2-20 and Comparative Examples 1-4 Examples 2-20 and Comparative Examples 1-4 each provide a secondary battery, differing from Example 1 only in the preparation process parameters and characteristic parameters of the resulting secondary battery. The preparation process parameters of the secondary battery are as follows: In Example 2, in step S21, pyromellitic acid and bipyridine were selected as organic ligands. Pyromellitic acid, bipyridine, and copper nitrate were added to the solvent in a molar ratio of 1:1:2. The reaction temperature in step S21 was 160°C. In step S22, graphene was selected as a reinforcing agent. The mass ratio of metal-organic framework material to binder was 12.3:1. Based on the sum of the masses of metal-organic framework material, reinforcing agent, binder PVDF, and dispersant PVP, the mass percentage of reinforcing agent was 2.2%. In Example 3, the reaction temperature in step S21 was 133°C, and in step S22, graphene was selected as the reinforcing agent. The mass ratio of metal-organic framework material to binder was 12.8:1. Based on the sum of the masses of metal-organic framework material, reinforcing agent, binder PVDF and dispersant PVP, the mass percentage of reinforcing agent was 1.9%. In Example 4, the reaction temperature in step S21 was 124°C, and the mass ratio of metal-organic framework material to binder in step S22 was 11.8:1. Based on the sum of the masses of metal-organic framework material, reinforcing agent, binder PVDF, and dispersant PVP, the mass percentage of reinforcing agent was 2.4%. In Example 5, the reaction temperature in step S21 was 118°C, and in step S22, graphene was selected as the reinforcing agent. The mass ratio of metal-organic framework material to binder was 9.1:1. Based on the sum of the masses of metal-organic framework material, reinforcing agent, binder PVDF, and dispersant PVP, the mass percentage of the reinforcing agent was 3.6%. In Example 6, the reaction temperature in step S21 was 100°C, the mass ratio of metal-organic framework material to binder in step S22 was 10.3:1, and the mass percentage of the reinforcing agent was 3.1% based on the sum of the masses of metal-organic framework material, reinforcing agent, binder PVDF and dispersant PVP. In Example 7, bipyridine was selected as the organic ligand in step S21, and bipyridine and zinc nitrate were added to the solvent at a molar ratio of 1:2. The reaction temperature in step S21 was 157°C. In step S22, graphene was selected as the reinforcing agent, and the mass ratio of metal-organic framework material to binder was 14.7:1. Based on the sum of the masses of metal-organic framework material, reinforcing agent, binder PVDF, and dispersant PVP, the mass percentage of the reinforcing agent was 1.1%. In Example 8, terephthalic acid was selected as the organic ligand in step S21, and terephthalic acid and copper nitrate were added to the solvent in a molar ratio of 1:2. The reaction temperature in step S21 was 103°C. Graphene was selected as the reinforcing agent in step S22. The mass ratio of metal-organic framework material to binder was 9.2:1. Based on the sum of the masses of metal-organic framework material, reinforcing agent, binder PVDF, and dispersant PVP, the mass percentage of the reinforcing agent was 3.5%. In Example 9, bipyridine was selected as the organic ligand in step S21, and bipyridine and zinc nitrate were added to the solvent at a molar ratio of 1:2. The reaction temperature in step S21 was 194°C. In step S22, a mixture of graphene and carbon nanotubes at a mass ratio of 3:1 was selected as the reinforcing agent. The mass ratio of metal-organic framework material to binder was 8.7:1. Based on the sum of the masses of metal-organic framework material, reinforcing agent, binder PVDF and dispersant PVP, the mass percentage of the reinforcing agent was 3.8%. In Example 10, 2-methylimidazole was selected as the organic ligand in step S21, and 2-methylimidazole and aluminum nitrate were added to the solvent in a molar ratio of 1:3. The reaction temperature in step S21 was 70°C. Graphene was selected as the reinforcing agent in step S22. The mass ratio of metal-organic framework material to binder was 15.1:1. Based on the sum of the masses of metal-organic framework material, reinforcing agent, binder PVDF and dispersant PVP, the mass percentage of the reinforcing agent was 0.9%. In Example 11, bipyridine was selected as the organic ligand in step S21, and bipyridine and zinc nitrate were added to the solvent at a molar ratio of 1:2. The reaction temperature in step S21 was 163°C. In step S22, the mass ratio of metal-organic framework material to binder was 15.9:1. Based on the sum of the masses of metal-organic framework material, reinforcing agent, binder PVDF and dispersant PVP, the mass percentage of reinforcing agent was 0.5%. In Example 12, bipyridine was selected as the organic ligand in step S21, and bipyridine and zinc nitrate were added to the solvent at a molar ratio of 1:2. The reaction temperature in step S21 was 169°C. In step S22, the mass ratio of metal-organic framework material to binder was 14.9:1. Based on the sum of the masses of metal-organic framework material, reinforcing agent, binder PVDF, and dispersant PVP, the mass percentage of reinforcing agent was 1%. In Example 13, bipyridine was selected as the organic ligand in step S21, and bipyridine and zinc nitrate were added to the solvent at a molar ratio of 1:2. The reaction temperature in step S21 was 198°C. In step S22, graphene was selected as the reinforcing agent, and the mass ratio of metal-organic framework material to binder was 15.4:1. Based on the sum of the masses of metal-organic framework material, reinforcing agent, binder PVDF, and dispersant PVP, the mass percentage of the reinforcing agent was 0.8%. In Example 14, 2-methylimidazole was selected as the organic ligand in step S21. 2-methylimidazole and aluminum nitrate were added to the solvent in a molar ratio of 1:3. The reaction temperature in step S21 was 63°C. In step S22, the mass ratio of the metal-organic framework material to the binder was 8.2:1. Based on the sum of the masses of the metal-organic framework material, reinforcing agent, binder PVDF, and dispersant PVP, the mass percentage of the reinforcing agent was 4%. In Example 15, 2-methylimidazole was selected as the organic ligand in step S21, and 2-methylimidazole and aluminum nitrate were added to the solvent in a molar ratio of 1:3. The reaction temperature in step S21 was 78°C. Graphene was selected as the reinforcing agent in step S22. The mass ratio of metal-organic framework material to binder was 6.2:1. Based on the sum of the masses of metal-organic framework material, reinforcing agent, binder PVDF and dispersant PVP, the mass percentage of the reinforcing agent was 4.8%. In Example 16, 2-methylimidazole was selected as the organic ligand in step S21, and 2-methylimidazole and aluminum nitrate were added to the solvent in a molar ratio of 1:3. The reaction temperature in step S21 was 93°C. Graphene was selected as the reinforcing agent in step S22. The mass ratio of metal-organic framework material to binder was 7.8:1. Based on the sum of the masses of metal-organic framework material, reinforcing agent, binder PVDF and dispersant PVP, the mass percentage of the reinforcing agent was 4.2%. In Example 17, 2-methylimidazole was selected as the organic ligand in step S21, and 2-methylimidazole and aluminum nitrate were added to the solvent in a molar ratio of 1:3. The reaction temperature in step S21 was 93°C. Graphene was selected as the reinforcing agent in step S22. The mass ratio of metal-organic framework material to binder was 6.1:1. Based on the sum of the masses of metal-organic framework material, reinforcing agent, binder PVDF and dispersant PVP, the mass percentage of reinforcing agent was 4.9%. In Example 18, bipyridine was selected as the organic ligand in step S21, and bipyridine and zinc nitrate were added to the solvent at a molar ratio of 1:2. The reaction temperature in step S21 was 185°C. In step S22, the mass ratio of metal-organic framework material to binder was 16:1. Based on the sum of the masses of metal-organic framework material, reinforcing agent, binder PVDF and dispersant PVP, the mass percentage of reinforcing agent was 0.5%. In Example 19, 2-methylimidazole was selected as the organic ligand in step S21. 2-methylimidazole and aluminum nitrate were added to the solvent in a molar ratio of 1:3. The reaction temperature in step S21 was 60°C. In step S22, the mass ratio of the metal-organic framework material to the binder was 10:1. Based on the sum of the masses of the metal-organic framework material, reinforcing agent, binder PVDF, and dispersant PVP, the mass percentage of the reinforcing agent was 3.1%. In Example 20, bipyridine was selected as the organic ligand in step S21, and bipyridine and zinc nitrate were added to the solvent at a molar ratio of 1:2. The reaction temperature in step S21 was 200°C. Graphene was selected as the reinforcing agent in step S22. The mass ratio of metal-organic framework material to binder was 15.3:1. Based on the sum of the masses of metal-organic framework material, reinforcing agent, binder PVDF, and dispersant PVP, the mass percentage of the reinforcing agent was 0.8%. In Comparative Example 1, 2-methylimidazole was selected as the organic ligand in step S21. 2-methylimidazole and aluminum nitrate were added to the solvent in a molar ratio of 1:3. The reaction temperature in step S21 was 67°C. In step S22, the mass ratio of metal-organic framework material to binder was 6.3:1. Based on the sum of the masses of metal-organic framework material, reinforcing agent, binder PVDF, and dispersant PVP, the mass percentage of reinforcing agent was 4.7%. In Comparative Example 2, bipyridine was used as the organic ligand in step S21, and bipyridine and zinc nitrate were added to the solvent at a molar ratio of 1:2. The reaction temperature in step S21 was 196℃. In step S22, graphene was used as the reinforcing agent, and the mass ratio of metal-organic framework material to binder was 15.8:1. Based on the sum of the masses of metal-organic framework material, reinforcing agent, binder PVDF, and dispersant PVP, the mass percentage of the reinforcing agent was 0.6%. In Comparative Example 3, 2-methylimidazole was selected as the organic ligand in step S21, and 2-methylimidazole and aluminum nitrate were added to the solvent in a molar ratio of 1:3. The reaction temperature in step S21 was 66℃. Graphene was selected as the reinforcing agent in step S22. The mass ratio of metal-organic framework material to binder was 6:1. Based on the sum of the masses of metal-organic framework material, reinforcing agent, binder PVDF and dispersant PVP, the mass percentage of the reinforcing agent was 5%. In Comparative Example 4, bipyridine was selected as the organic ligand in step S21. Bipyridine and zinc nitrate were added to the solvent at a molar ratio of 1:2. The reaction temperature in step S21 was 200℃. In step S22, the mass ratio of metal-organic framework material to binder was 15.8:1. Based on the sum of the masses of metal-organic framework material, reinforcing agent, binder PVDF and dispersant PVP, the mass percentage of reinforcing agent was 0.6%.
[0127] The characteristic parameters of the secondary batteries obtained from the above embodiments and comparative examples are shown in Table 1.
[0128] The energy density and fast charging performance of the secondary batteries obtained in the above embodiments and comparative examples are shown in Table 1.
[0129] Table 1 As shown in Table 1, the embodiments of this application, by comprehensively controlling the average pore size (rnm) of the metal-organic framework material and the Young's modulus (EGPa) of the negative electrode coating, keep the E / r within a suitable range. This better balances the lithium storage space and structural strength of the negative electrode coating, allowing the negative electrode sheet to be used in secondary batteries while maintaining both energy density and kinetic performance. The energy density of the secondary battery is no less than 314.5 Wh / kg, and the fast charging time is no more than 27.9 min. When the E / r is between 1.9 and 12.8, the overall improvement in energy density and fast charging performance of the secondary battery is even better.
[0130] Compared with the embodiments, the E / r ratio in Comparative Example 1 is too high, resulting in a significant decrease in the energy density of the secondary battery.
[0131] Compared with the embodiments, the E / r ratio in Comparative Example 2 is too small, resulting in a significant decrease in the fast charging performance of the secondary battery.
[0132] Compared with the embodiments, in Comparative Example 3, r is too small and E / r is too large, resulting in a significant decrease in the energy density of the secondary battery, even lower than that of Comparative Example 1.
[0133] Compared with the embodiments, in Comparative Example 4, r is too large and E / r is too small, resulting in a significant decrease in the fast charging performance of the secondary battery, which is even worse than that of Comparative Example 3.
[0134] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application and are not intended to limit the scope of protection of this application. Although this application has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of this application without departing from the substance and scope of the technical solutions of this application.
Claims
1. A negative electrode sheet, characterized in that, The negative electrode includes a negative current collector and a negative electrode coating disposed on at least one side of the negative current collector. The negative electrode coating includes a metal-organic framework material. The Young's modulus of the negative electrode coating is E GPa, and the average pore size of the metal-organic framework material is r nm. The negative electrode sheet satisfies the following condition: E / r is 0.7~33.
2. The negative electrode sheet as described in claim 1, characterized in that, E / r ranges from 1.9 to 12.
8.
3. The negative electrode sheet as described in claim 1, characterized in that, E GPa is 3GPa~20GPa, and / or r nm is 0.5nm~5nm.
4. The negative electrode sheet as described in claim 1, characterized in that, The compaction density of the negative electrode sheet is 0.8 g / cm³. 3 ~1.5g / cm 3 .
5. The negative electrode sheet as described in claim 1, characterized in that, The metal-organic framework material comprises an organic ligand and a metal ion, wherein the organic ligand has a structural formula including a conjugated group, and the conjugated group includes at least one of a benzene ring, a fused ring, and a carbon-carbon double bond group.
6. The negative electrode sheet as described in claim 5, characterized in that, The organic ligand includes at least one of a carboxylic acid-containing organic ligand and a nitrogen-containing heterocyclic organic ligand, wherein the carboxylic acid-containing organic ligand includes at least one of terephthalic acid and trimesoic acid, and the nitrogen-containing heterocyclic organic ligand includes at least one of 2-methylimidazole and bipyridine.
7. The negative electrode sheet as described in claim 5, characterized in that, The metal ions include at least one of aluminum ions, zirconium ions, zinc ions, and copper ions.
8. The negative electrode sheet as described in claim 1, characterized in that, The metal-organic framework material includes at least one of MIL-101, MIL-53, ZIF-7, ZIF-8, and ZIF-67.
9. The negative electrode sheet as described in claim 1, characterized in that, The negative electrode coating also includes doping elements; The doping element includes at least one of nitrogen, boron, sulfur and phosphorus, and / or the mass percentage of the doping element in the negative electrode coating is 0.5% to 5%.
10. The negative electrode sheet as described in claim 1, characterized in that, The thickness of the negative electrode coating is 1μm to 10μm.
11. The negative electrode sheet as described in claim 1, characterized in that, The porosity of the negative electrode coating is 20%~60%.
12. The negative electrode sheet as described in claim 1, characterized in that, The negative electrode current collector includes copper foil, which includes at least one of porous copper foil, etched copper foil, and copper foil with a lithium-loving coating on its surface, wherein the lithium-loving coating includes at least one of carbon and gold.
13. A secondary battery, characterized in that, The device includes the negative electrode sheet as described in any one of claims 1 to 12, and further includes the positive electrode sheet, the separator, and the electrolyte.
14. The secondary battery as described in claim 13, characterized in that, The compaction density of the positive electrode is 3 g / cm³. 3 ~4.2g / cm 3 .
15. The secondary battery as described in claim 13, characterized in that, The positive electrode sheet includes a positive electrode material layer, the positive electrode material layer includes a positive electrode material, and the particle size Dv50 of the positive electrode material is 3μm~12μm.
16. The secondary battery as described in claim 15, characterized in that, The cathode material includes at least one of lithium manganese iron phosphate, lithium iron phosphate, and nickel-cobalt ternary materials.
17. The secondary battery as described in claim 16, characterized in that, The positive electrode material is at least one of lithium manganese iron phosphate and lithium iron phosphate, and the thickness of the negative electrode coating is 1μm~4μm; Alternatively, the positive electrode material is a nickel-cobalt ternary material, and the thickness of the negative electrode coating is 3μm~8μm.
18. The secondary battery as described in claim 15, characterized in that, The surface of the positive electrode material is provided with a coating layer, the thickness of which is 1 nm to 10 nm.
19. The secondary battery as described in claim 15, characterized in that, The cathode material layer includes doped elements; The doping element includes at least one of Al, Mg, Ti, Zr, B, and Y, and / or the mass percentage of the doping element in the cathode material layer is 0.1% to 3%.
20. The secondary battery as described in claim 15, characterized in that, The cathode material includes lithium iron phosphate, which comprises ultra-large particles, large particles, and small particles. The ultra-large particles have a particle size of 3~15μm, the large particles have a particle size of 1μm~3μm, and the small particles have a particle size of 60nm~200nm.
21. The secondary battery as described in claim 13, characterized in that, The viscosity of the electrolyte at 25°C is 3 mPa·s to 15 mPa·s.
22. The secondary battery as described in claim 13, characterized in that, The electrolyte includes lithium salt; The lithium salt includes at least one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium perchlorate, lithium tetrafluoroborate, lithium dioxalate borate, lithium difluorooxalate borate, lithium trifluoromethanesulfonate, lithium difluoromethanesulfonylimide, lithium ditrifluoromethanesulfonylimide, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate, and / or the concentration of the lithium salt in the electrolyte is 0.8 mol / L to 1.5 mol / L.
23. The secondary battery as described in claim 13, characterized in that, The air permeability of the diaphragm is 200s / 100mL to 500s / 100mL.
24. An electrical appliance, characterized in that, Includes the secondary battery as described in any one of claims 13 to 23.